SpeI restriction enzyme displays greater discriminatory power than XbaI enzyme does in a pulsed-field gel electrophoresis study on 146 clinical burkholderia pseudomallei isolates - Chua, K.H.; See, K.H.; Thong, Kwai Lin; Puthucheary, S.D. (Institute of Infectious Diseases, 2011)
Restriction enzymes SpeI and XbaI were used in a pulsed-field gel electrophoresis (PFGE) study for molecular characterization of 146 clinical Burkholderia pseudomallei isolates. The PFGE parameters were optimized to enable comparable, reproducible, and robust results. The optimized parameters for both SpeI and XbaI restriction enzymes used in this study were 200 V and a pulse time of 5 to 65 s for a 28-h runtime. Using SpeI, 9 different clusters were identified, whereas 6 clusters were identified by XbaI digestion, which exhibited 85 similarity to SpeI. SpeI (discrimination index D=0.854) showed higher discriminatory power than XbaI did (D=0.464).